PENGARUH PERENDAMAN BAMBU PETUNG,BAMBU HITAM DAN BAMBU APUS DI AIR RAWA - Nurul Asni; Djonaedi Saleh; Abrarsyah Algamar (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Soaking bamboo in swamp water serves to prolong the use of materials in the building structure. Soaking bamboo in swamp water was conducted for 60 days with an interval of 5 days. The longer soaking the bamboo then the stronger termite pest resistance. After bamboo was soaking for 15 days, termites did not want to eat bamboo. This situation is caused by methyl (CH3) which occurs due to the reaction between cellulose with methane in the swamp water. Bending test of bamboo which soaked in swamp water obtained the increase in modulus elasticity of before it soaked such as bamboo petung which increase from 411MPa to 513 MPa, bamboo hitam from 411 to 494 MPa and bamboo apus from 411 to 621MPa after. However Tensile strength of those three bamboo was decreased through increasing time of soaking. For instance Bamboo petung’s tensile strength was descerase from 95.3 MPa to 26.7 Mpa, bamboo hitam from 104.2 MPa to 52.6 Mpa and bamboo apus from 93.7 MPa to 43.2 Mpa.Keywords: bamboo, soaking swamp water, tensile strength, modulus of elasticity.